2016
DOI: 10.1007/s11626-016-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5

Abstract: Development of skeletal muscle is a complicated biological process regulated by various regulation factors and signal pathways. MicroRNAs (miRNAs) are novel gene regulators that control muscle cell development. microRNA-143 (miR-143) is highly expressed in skeletal muscle, and we found that miR-143 level is significantly increased during bovine skeletal muscle satellite cells (MSCs) differentiation process through microarray analysis and qRT-PCR detection. However, the function of miR-143 in bovine muscle deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In mouse mammary gland, IGFBP-5 expression is suppressed by the hormone prolactin and STAT-3 (32,36,37). IGFBP-5 mRNA has also been found to be regulated by several miRNAs (37)(38)(39)(40).…”
Section: Expression and Regulationmentioning
confidence: 99%
“…In mouse mammary gland, IGFBP-5 expression is suppressed by the hormone prolactin and STAT-3 (32,36,37). IGFBP-5 mRNA has also been found to be regulated by several miRNAs (37)(38)(39)(40).…”
Section: Expression and Regulationmentioning
confidence: 99%
“…IGFBP5, an inhibitory binding protein with affinity for IGF, is highly upregulated in nerve biopsies of patients with diabetic neuropathy. Zhang WR et al have showed that miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5, 36 miR-143 also directly regulates the expression of IGFBP5 during muscle regeneration. 37 No mechanism of action or function of IGFBP5 in insulin signaling and MetS patients was elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This then allows the binding proteins to influence IGFs, either by altering IGF actions or by switching on IGF‐II . The regulation of IGFBP‐5 is more elusive but studies point to regulation by key microRNAs like miR‐140 …”
Section: Discussionmentioning
confidence: 99%